Copeptin combined with either non-high sensitivity or high sensitivity cardiac troponin for instant rule-out of suspected non-ST segment elevation myocardial infarction. (16th November 2020) - Giannitsis, Evangelos; Slagman, Anna; Hamm, Christian W.; Gehrig, Stefan; Vollert, Joern O.; Huber, Kurt
Abstract: Background: Whether Copeptin combined with high sensitivity troponin below the respective decision cut-offs improves rule-out of NSTEMI and may predict all-cause death at 30-day is under debate. Methods: Data on 10, 329 patients from 5 trials were pooled to evaluate the diagnostic and prognostic performance of an initial Copeptin below decision cut-off in combination with a (hs)-cTn below the uppler limit of normal (ULN) compared to a) the initial (hs)-cTn alone in the standard serial sampling strategy based on the 99th percentile and b) a single marker strategy (SMS) based on hs-cTn < limit of detection. Endpoints were sensitivities and negative predictive values (NPV) for rule-out of NSTEMI, 30-day all-cause mortality and rates of eligibility for DMS or SMS. Results: NPV for NSTEMI was higher for DMS than for the initial cTn, regardless assay sensitivity. The highest NPVs were observed with DMS vs. hs-cTn (99.4% [95% CI: 99.0%–99.6%] vs. 98.8% [98.4%–99.1%], ), and improved performance was consistent across all important subgroups including presentation <3 h, again irrespective of assay sensitivity. The point estimate of all NPVs for all-cause death exceeded 99.75%. In the label populations, DMS versus SMS demonstrated comparably high NPVs for rule-out of NSTEMI (99.4% [99.0%–99.6%] vs. 99.9% [99.2%–100.0%]), very low mortality after rule-out (0.1% [0.0%–0.4% vs. 0.0% [0.0%–1.2%]), but eligibility for rule-out was 2.4-fold higher (61.4% [59.9%–62.9%] vs. 25.3% [23.7%–26.9%]) with DMS than SMS. Conclusion: Findings from a large pooled cohort corroborate the safety of the dual marker strategy for instant rule-out of NSTEMI, extending evidence to hs-cTn. Copeptin below cut-off in combination with hs-cTn below ULN may be used in more than 2.4-times more patients presenting with suspected ACS than a single marker strategy based on very low hs-cTn, without the need to exclude very early presenters or other important subgroups.